Green Technologies for Sustainable Development - Sharma, Narendra (India : Discovery Publishing House, 2023)
Over many decades of implementation, we have learned that environmental protection can never be sufficiently developed and promoted. Because the world is currently coping with increasingly critical environmental concerns, it is imperative that we intensify our efforts to promote and enhance environmental protection. This book has been arranged for young researchers from various universities and colleges in accordance with the most recent developments in green technologies. We are confident that new edition of the book will be more valuable to all researchers who have been involved in scientific study given the latest information on many elements of sciences.
Includes index.
Keywords: Green technology; Pollution; Environmental monitoring; Waste management